2016
DOI: 10.1113/ep085803
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen upregulates the expression levels and functional activities of duodenal mucosal CFTR and SLC26A6

Abstract: What is the central question of this study? Duodenal ulcer is a common disease. A sex-based difference in the incidence of duodenal ulcer has long been observed clinically, but the cause is unclear. What is the main finding and its importance? Duodenal mucosal bicarbonate secretion is the most important protective factor in duodenal mucosa against acid-induced damage. The cystic fibrosis transmembrane conductance regulator (CFTR) and the solute-linked carrier 26 gene family A6 (SLC26A6) are two key bicarbonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
7
0
2
Order By: Relevance
“…This was corroborated by E2 treatment of OVX rats that mimicked the results of OHSS and through measurement of CFTR activity in freshly isolated uterine epithelia [204]. In another study, CFTR expression was higher in women than in men in duodenal mucosa cells and in duodenocytes treated with E2 (1 nM) for 12 h, where a significant increase in expression mediated by ERα was observed [205]. This was also corroborated by measuring the activity of CFTR in OVX mice.…”
Section: Cystic Fibrosis Transmembrane Conductance Regulatormentioning
confidence: 59%
See 1 more Smart Citation
“…This was corroborated by E2 treatment of OVX rats that mimicked the results of OHSS and through measurement of CFTR activity in freshly isolated uterine epithelia [204]. In another study, CFTR expression was higher in women than in men in duodenal mucosa cells and in duodenocytes treated with E2 (1 nM) for 12 h, where a significant increase in expression mediated by ERα was observed [205]. This was also corroborated by measuring the activity of CFTR in OVX mice.…”
Section: Cystic Fibrosis Transmembrane Conductance Regulatormentioning
confidence: 59%
“…This was also corroborated by measuring the activity of CFTR in OVX mice. Forskolin (a CFTR activator) stimulation response was markedly decreased, and this effect was reverted with E2 supplementation [205]. Similarly, peritoneal epithelial cells of rats with induced OHSS showed CFTR upregulation, and this genomic effect was reproduced by E2 treatment in OVX rats [206].…”
Section: Cystic Fibrosis Transmembrane Conductance Regulatormentioning
confidence: 99%
“…Felix Knauf et al ( 108 ) found that the expression of SLC26A6 decreased in the duodenum of CFTR gene-deficient mice, intestinal oxalate secretion decreased significantly, and the deficient mice exhibited hyperoxalemia and hyperoxaluria. Estradiol can up-regulate CFTR on the surface of intestinal mucosal cells to increase the expression of SLC26A6 and regulate oxalate transport ( 109 , 110 ). Therefore, CFTR may be an upstream protein of SLC26A6.…”
Section: Slc26a6-mediated Regulation Of Oxalate Transportmentioning
confidence: 99%
“…Farmakokinetske polne razlike koje se odnose na resorpciju leka mogu se pripisati razlikama u nivou sekrecije želudačne kiseline, a pojedine studije navode da je ona niža kod žena [6], brzini pražnjenja sadržaja iz želuca, na šta imaju uticaj polni hormone [7], sastavu duodenalnog soka [8] (kod premenopauzalnih žena povećana sekrecija bikarbonata u duodenumu u odnosu na muškarce, takođe zbog uticaja polnih hormona), nivou ekspresije P-glikoproteina u tankom crevu. Mada bi se to moglo očekivati obzirom na to da su steroidni polni hormoni supstrati za P-glikoprotein [9], to u nekim istraživanjima nije potvrđeno [10].…”
Section: Uvodunclassified